Bone conductive implants in single-sided deafness. (April 2015) - Monini, Simonetta; Musy, Isotta; Filippi, Chiara; Atturo, Francesca; Barbara, Maurizio
Abstract: Conclusion: Bone conduction implants (BCIs) have been shown to partially restore some of the functions lost when binaural hearing is missing, such as in subjects with single-sided deafness (SSD). The use of a single BCI needs to be recommended by a clinician based on thorough counselling with the SSD subject. Objectives: To perform an overview of the present capabilities of BCIs for SSD and to evaluate the reliability of the audiological evaluation for assessing speech recognition in noise and sound localization cues, which are major problems related to the loss of binaural hearing. Methods: Nine subjects with SSD who received BCI implants underwent a preoperative audiological evaluation that included sound field speech audiometry, word recognition score (WRS) testing and sound localization testing in quiet and in noise. They were also tested for the accuracy of their directional word recognition in noise and their subjective perceptions of their hearing difficulties using the APHAB questionnaire. Results: The mean maximum accuracy of word discrimination was 65.5% in the unaided condition and 78.9% in the BCI-aided condition. Sound localization in noise was better with the BCI than in the unaided condition, especially when the stimulus and noise were presented on the same side as the implanted ear. The accuracy of directional word recognition showed an improvement with the BCI with respect to the unaided condition on the BCI side, with either the stimulus in the implanted ear and the noise in the contralateral ear or with both the stimulus and noise presented to the implanted ear.